"Protein-Energy Malnutrition in School Children of Boirahmad Rural Areas, Iran" - JM Malekzadeh; E Hatamipour; E Afshoon (Tehran University of Medical Sciences, 2003)
Growth monitoring is very important in nutritional assessment of children up to the age of maturity. Based on studies in Kohgiluyeh-Boirahmad province, many of under five years old children are suffering from protein- energy malnutrition, although the nutritional conditions of school children are unknown. This study was performed to determine the prevalence of protein- energy malnutrition in rural school children of Boirahmad. 544 school children were selected from eleven rural primary schools. Weight and height were measured with 0.1 kg and 0.5-centimeter precision, respectively. Nutritional indices including height for age, weight for age and weight for height were determined using EPI6 software and compared with relative NCHS standards. Based on -2 SD cut of point for indices, 15.7 %( CI=12.6- 18.8), 12.5 %( CI=9.9-15.5) and 3.6 %( CI= 2-5.2) of children were suffering from stunting, underweight and wasting respectively. Girls were better than boys in height for age. Parents' education and father job had significant association with height for age. Results suggest that stunting, an important form of protein- energy malnutrition is moderately prevalent in Boirahmadian school children, but to determine the causes, more studies are suggested.